The Mediating Effects of Self-Efficacy on Entrepreneurship Education and Student’s Entrepreneurial Intention - Karen De Leon; Edilberto Z. Andal; Edna O. Briones (Journal of General Education and Humanities, 2023)
To those pursuing careers in business disciplines, entrepreneurship education has become crucial. Based on entrepreneurship education philosophy, this study examines how learning and intention affect secondary students' entrepreneurial goals, especially those of Malvar School of Arts and Trade students in Grade 10. This tackles the scarcity of research on the role of self-efficacy as a mediator between entrepreneurial intention and entrepreneurship education. The descriptive correlational method of research was utilized in this study. The primary tool for collecting data was the questionnaire created by the researcher. Respondents were 198 Grade 10 students at Malvar School of Arts and Trade. The respondents believed entrepreneurship education and self-efficacy strengthened their intention to become entrepreneurs. They also believed that entrepreneurship education increases their understanding of starting their enterprise. Between entrepreneurship education and entrepreneurial intention, self-efficacy plays a crucial role, enabling students to anticipate when they will start a new firm.